Influencia de la televisión en el Rendimiento Académico de los niños de 5 años de la Institución Educativa Inicial Nº 288 de la provincia de Rioja en al año 2003 - Bazán Figueroa, Judith Marleni (2005)
Since the television appeared being part of the man's daily life in the society, it has been able to modify it is life in significant form, he/she has even entered in each one of the homes, where it has surrounded the attention especialty of the children and girls becoming until our time one of its favorite entertainments, so much that it has ended up interfering with a lot of force In the school activities affecting in diverse ways the learning. This preocupante situation took us to think about the problem of the influence of Television in the Academic Yield, guiding us to demonstrate that in the event of an excess one would have a faulty academic acting through a design correlacional that contrasted the two variables involved in the study for an equivalent population of 110 year-old 5 students. Procedimentalmente was necessary first to determine the frequency of the use of television of the children qualitatively, tha.t is to say which is the certain time that the children accustom to see television, this with regard to the first variable. The second variable was only measured appealing to the epithets of the records of the students' escolaridad according to the design you the one proceeded to the correlation which threw the absence of the same one. The analytic process of the results demonstrated that the students indeed make excessive use of television in the studied population, however, it is not enough cause to cause a decrease in the academic yield of the students, since the entirety of students conformantes of the sample, they present a satisfactory and approbatory escolaridad situation . lt is believed that the informative system of the school evaluation that is managed at the moment doesn't reflect specific qualitative components , for what negative indicators are not noticed as those that can produce the television in the boy's formation, being able to go by desapercibido serious situations of negative